Integration of an individual-oriented model into a system dynamics model: An application to a multi-species system. (February 2019) - Kim, Yongeun; Son, Jino; Lee, Yun-Sik; Lee, Minyoung; Hong, Jinsol; Cho, Kijong
Abstract: Although the system dynamics (SD) modeling approach has been used frequently to model various systems, there is little research on the development of hybrid SD–individual-oriented (IO) modeling. The aim of this study is to demonstrate the use of an array variable for the hybrid SD–IO modeling approach using the SD platform, and to provide a detailed modeling process of an algae–daphnid system consisting of two freshwater algal species and Daphnia . Our study showed that the array variable in the SD approach is useful for modeling multiple individuals and as a function to control the switch and integration variable for the hybrid modeling approach. The proposed method can improve the usability of hybrid modeling by enabling hybrid SD–IO modeling without requiring extensive knowledge of programming. Given the ongoing development and advancement of the SD modeling approach, this modeling technique will be a useful method to study complex systems. Highlights: The method for hybrid system dynamics (SD)–individual-oriented (IO) approach using the SD platform was demonstrated. For IO modeling in the SD approach, multiple individuals were modeled using array variables. To implement the proposed method, the algae–daphnid system was chosen as the subject of the case study. The results showed that the method can be a useful approach for combining SD and IO models in a single modeling platform.